Measuring Cooperative Biological Engagement Program (CBEP) Performance Capacities, Capabilities, and Sustainability Enablers for Biorisk Management and Biosurveillance - Young, Stephanie (RAND Corporation, 2014)
The Cooperative Biological Engagement Program partners with about 20 countries in different regions around the world and works with them to address diverse threats to international security. This report describes a project to develop a comprehensive evaluation framework and recommends metrics for assessing and communicating progress toward the program's goals.